Primer informe de virus infectando cártamo en Argentina - Cabrera Mederos, Dariel; Cerrotta, A.; Lindström, L.I.; Trucco, Veronica Milagros; Castellanos Collazo, Onias; Giolitti, Fabian (Asociación Argentina de Fitopatólogos, 2021)
Poster